2015
DOI: 10.1017/s0021859615000799
|View full text |Cite
|
Sign up to set email alerts
|

Predicting global geographical distribution of Lolium rigidum (rigid ryegrass) under climate change

Abstract: Lolium rigidum L. (rigid ryegrass) is one of the most extensive and harmful weeds in winter cereal crops. A bioclimatic model for this species was developed using CLIMEX. The model was validated with records from North America and Oceania and used to assess the global potential distribution of L. rigidum under the current climate and under two climate change scenarios. Both scenarios represent contrasting temporal patterns of economic development and carbon dioxide (CO 2 ) emissions. The projections under curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…For instance, Castellanos-Frías et al (2016) reported that the geographic distribution of L. rigidum in Europe is expected to change, expanding to regions that are currently too cold for its survival but may not be in the near future. According to Castellanos-Frías et al (2016), suitable regions in Europe for this weed species are predicted to increase by 108.7 or 167.3% depending on different climate change scenarios. Climate change can also influence the geographical distribution of crops and their losses caused by A. myosuroides.…”
Section: Effects Of Climate Change On Weed Distribution and Vegetablementioning
confidence: 99%
See 3 more Smart Citations
“…For instance, Castellanos-Frías et al (2016) reported that the geographic distribution of L. rigidum in Europe is expected to change, expanding to regions that are currently too cold for its survival but may not be in the near future. According to Castellanos-Frías et al (2016), suitable regions in Europe for this weed species are predicted to increase by 108.7 or 167.3% depending on different climate change scenarios. Climate change can also influence the geographical distribution of crops and their losses caused by A. myosuroides.…”
Section: Effects Of Climate Change On Weed Distribution and Vegetablementioning
confidence: 99%
“…If these projections are realized, it is anticipated that significant changes in weed flora composition and distribution will take place throughout Europe (Fig. 3) and other parts of the globe (McDonald et al ., 2009; Castellanos-Frías et al ., 2016). Predicting weed invasion in a specific region undergoing climate change is a major challenge (Clements and DiTommaso, 2012).…”
Section: Effects Of Climate Change On Weed Distribution and Vegetablementioning
confidence: 99%
See 2 more Smart Citations
“…Rigid ryegrass has many features that contribute to the evolution of resistance, including i) a very well adapted species to the Mediterranean climate, ii) a propensity to occur in large densities, iii) the high genetic diversity within populations, iv) a self-incompatibility and cross-pollinated species, v) the potential to set a large amount of seed, allowing any resistant survivors to significantly increase the resistance status of a population, vi) the short-lived innate dormancy, which results in a large amount of the seedbank germinating in the next season, vii) the short soil seedbank life, and viii) the ability to rapidly evolve resistance to herbicides (Castellanos-Frias et al, 2016;Bararpour et al, 2017).…”
Section: Introductionmentioning
confidence: 99%